Pharmacological Approaches To Infectious Diseases Exploring Microbial Pathways For Enhanced Therapeutic Solutions - Zakaraya, Zainab Z.; Delgado, Adalberto Emilio Llinas; Dayyih, Wael Abu; Sood, Dr Shilpa Khullar; Agrawal, Dr. Darpan; Paul, Dr. Swarnali Das (South Eastern European Journal of Public Health, 2024)
The problem of antibiotics resistance in healthcare is getting more and more noticeable and the look for alternative therapy is among the measures that we need to use against the infectious diseases. The review will focus on the new drug approaches which disrupt the microbial pathways and are expected to resolve this modern-day challenge. Conventional microorganism-killers are becoming less effective. A quest for alternative action must be undertaken. Three promising approaches are discussed: therapeutic modalities for instance, antimicrobial oligonucleotides, monoclonal antibodies, and phage therapy. Antimicrobial oligonucleotides are an altogether different category from other options as they work against a broad spectrum of organisms with the least development of resistance, making them a promising option. The phage therapy involving mutation might influence the bacteria's genes to become resistant, but it is a renewable and cost-effective strategy with the ability to fight against the biofilm-associated infections. Monoclonal antibodies although experiencing challenges to access bacteria of some variety’s toxoids, defeat them by getting to effective toxins and virulence factors. The discussion focused on multidimensional methods of fighting microorganisms which compatible with both physical and genetic diversity of microorganisms, and stress on the availability of scientific and financial support for these innovative treatments. Emphasizing the scope of revolutionary pharmacological solutions, this article helps come of new strategies for infectious disease treatment next time. Thus, the review reemphasizes the urgency of exploring microbial pathways to unveil advanced drug delivery solutions. It promotes further research and funding in the advent of new treatment approaches that are needed to combat antibiotic resistance and address the cast-iron health dilemma in this region.